AB42 and polyamines: Elucidating a potential mechanism of amyloid‐mediated apoptosis and aggregation: Molecular and cell biology/APP/Abeta/amyloid. (7th December 2020) - Sandberg, Alexandra A.; Johnson, Austin; Fudge, Dylan; Melgar, Stephanie; Hicks, Carrie; Patterson, David; Vacano, Guido; Margittai, Martin; Weismiller, Hilary; Harvey, Sebastian; Hernandez, Luis; Caviedes, Pablo; et al.
Abstract: Background: The dysfunctional accumulation of amyloid beta (Aβ) plaques in neuronal cells is widely regarded as a hallmark sign of Alzheimer's disease (AD). However, the mechanisms by which Aβ causes the rampant apoptosis that leads to the characteristic memory loss and dementia observed in AD patients are much less understood. In this study, we investigated the regulatory relationship between Aβ42, a particularly toxic member of the Aβ peptide family, and polyamines (PA), a ubiquitous class of molecules associated with cell growth, proliferation, and immune response. Increasing evidence has suggested that the PA pathway is changed in AD. For example, increased levels of enzymes in the PA synthesis pathway and altered PA metabolomics have been found in the AD brain. Here, we sought to investigate the relationship between PA synthesis and disease pathogenesis, specifically Aβ aggregation and in turn, neuronal death. Method: HT22 hippocampal cells were transiently transfected with bicistronic plasmids allowing for expression of DsRed alone or co‐expression with Aβ42. We then examined the effects of Aβ42 on expression of the rate limiting enzyme for PA synthesis, ornithine decarboxylase (ODC) and in turn, PA levels. Irreversible ODC inhibitor, L‐difluoromethylornithine (DFMO) was used to examine effects on Aβ42 aggregation and neuronal apoptosis. Hippocampal tissue from human sporadic AD and age matched controls were also assessed for PA concentration and ODC expression. Results: We found that Aβ42 increased PA levels in a dose‐dependent fashion through enhanced expression of ODC in HT22 hippocampal cells. Treatment with DFMO significantly reduced this increase in PA as well as aggregation of Aβ42 and Aβ42 ‐induced apoptosis. Lastly, levels of spermidine and spermine as well as ODC expression were significantly increased in sporadic AD human hippocampal tissue in comparison to age‐matched controls. Conclusion: These data suggest that increased intracellular concentrations of PA are not only a response to Aβ42, but they also promote Aβ42 toxicity by enhancing aggregation. Secondarily, DFMO may be a novel therapeutic to mitigate Aβ42 toxicity and reduce amyloid plaque load in patients with AD.